Current Treatment Landscape of Nasopharyngeal Carcinoma and Potential Trials Evaluating the Value of Immunotherapy. (26th March 2019) - Le, Quynh Thu; Colevas, A Dimitrios; O'Sullivan, Brian; Lee, Anne W M; Lee, Nancy; Ma, Brigette; Siu, Lillian L; Waldron, John; Lim, Chwee-Ming; Riaz, Nadeem; Lynn, Jean; Malik, Shakun
Abstract: Nasopharyngeal carcinoma (NPC) is a type of head and neck cancer with a distinctive regional and racial prevalence. It is associated with Epstein-Barr virus infection and has a high propensity for regional and distant metastases, while it is very sensitive to radiation and chemotherapy. A common feature of Epstein-Barr virus-positive NPC is the dense infiltration of lymphocytes in the tumor stroma and positive programmed death-ligand 1 expression in tumor cells, making it an attractive target for immunotherapy, especially immune checkpoint inhibitors. As new immunotherapeutic agents are being rapidly adopted in many cancers, including head and neck cancer, the National Cancer Institute sponsored a clinical trial planning meeting to identify opportunities for developing phase II and III trials testing immunotherapy in different stages of NPC. The meeting started with the summary of the biology of the disease, current standards of care, and evidence of immunotherapy in this cancer. Three subcommittees were tasked to develop clinical trials: loco regionally advanced, nonmetastatic NPC; widely metastatic NPC; and either local recurrence after initial treatment or presenting with oligometastatic disease. This article summarizes the proceedings of this clinical trial planning meeting and provides a road map for future trials incorporating immune checkpoint inhibitors for therapeutic management of NPC. This road map, though specific for NPC, may also be applicable to other virally driven cancers that have similar ability to evade the host's immune system.